Genetic variations of the NPC1L1 gene associated with hepatitis C virus (HCV) infection and biochemical characteristics of HCV patients in China. (December 2016) - Zhang, A.-Mei; Zhang, Cheng-Lin; Song, Yuzhu; Zhao, Ping; Feng, Yue; Wang, Binghui; Li, Zheng; Liu, Li; Xia, Xueshan
Summary: Objectives: About 2% of the world population is infected with hepatitis C virus (HCV), a leading cause of hepatic cirrhosis and hepatocellular carcinoma. The Niemann–Pick C1-like 1 cholesterol absorption receptor (NPC1L1) was recently identified to be an important factor for HCV entry into host cells. Whether genetic variations of the NPC1L1 gene are associated with HCV infection is unknown. Methods: In this study, five single nucleotide polymorphisms (SNPs) of the NPC1L1 gene were analyzed in 261 HCV-infected individuals and 265 general controls from Yunnan Province, China. Results: No significant differences were identified in genotypes or alleles of the SNPs between the two groups. After constructing haplotypes based on the five SNPs, a significant difference between HCV-infected individuals and general controls was shown for two haplotypes. Haplotype GCCTT appeared to be a protective factor and haplotype GCCCT was a risk factor for HCV-infected individuals. Genotypes of four SNPs correlated with biochemical characteristics of HCV-infected persons. Genotypes of SNPs rs799444 and rs2070607 were correlated with total bilirubin. Genotype TT of rs917098 was a risk factor for the gamma-glutamyltransferase level. Furthermore, HCV-infected individuals carrying genotype GG of rs41279633 showed statistically higher gamma-glutamyltransferase levels than HCV-infected persons with GT and TT. Conclusion: The results of this study identified the association between genetic susceptibility of the NPC1L1 gene and HCV infection, as well as biochemical characteristics of HCV-infected persons in Yunnan, China.